Equity in healthcare financing: a case of Iran - Faride Sadat Jalali; Abdosaleh Jafari; Mohsen Bayati; Peivand Bastani; Ramin Ravangard (BMC, 2019)
Abstract Background Fair financial contribution in healthcare financing is one of the main goals and challengeable subjects in the evaluation of world health system functions. This study aimed to investigate the equity in healthcare financing in Shiraz, Iran in 2018. Materials and methods This was a cross- sectional survey conducted on the Shiraz, Iran households. A sample of 740 households (2357 persons) was selected from 11 municipal districts using the multi-stage sampling method (stratified sampling method proportional to size, cluster sampling and systematic random sampling methods). The required data were collected using the Persian format of "World Health Survey" questionnaire. The collected data were analyzed using Stata14.0 and Excel 2007. The Gini coefficient and concentration and Kakwani indices were calculated for health insurance premiums (basic and complementary), inpatient and outpatient services costs, out of pocket payments and, totally, health expenses. Results The Gini coefficient was obtained based on the studied population incomes equal to 0.297. Also, the results revealed that the concentration index and Kakwani index were, respectively, 0.171 and − 0.125 for basic health insurance premiums, 0.259 and − 0.038 for health insurance complementary premiums, 0.198 and − 0.099 for total health insurance premiums, 0.126 and − 0.170 for outpatient services costs, 0.236 and − 0.061 for inpatient services costs, 0.174 and − 0.123 for out of pocket payments (including the sum of costs related to the inpatient and outpatient services) and 0.185 and − 0.112 for the health expenses (including the sum of out of pocket payments and health insurance premiums). Conclusion The results showed that the healthcare financing in Shiraz, Iran was regressive and there was vertical inequity and, accordingly, it is essential to making more efforts in order to implement universal insurance coverage, redistribute incomes in the health sector to support low-income people, strengthening the health insurance schemes, etc.